Merkel Cell Carcinoma of the Retroperitoneum with No Identifiable Primary Site. (1st September 2013) - Rossini, Daniele; Caponnetto, Salvatore; Lapadula, Vittoria; De Filippis, Lucilla; Del Bene, Gabriella; Emiliani, Alessandra; Longo, Flavia
Abstract : Merkel cell carcinoma (MCC) is an extremely rare primary neuroendocrine neoplasm of the skin that shows aggressive behavior and a poor prognosis. We report a case of a 67-year-old male with a Merkel cell carcinoma which initially presented itself as a large retroperitoneal mass. Pathological and immunohistochemical analysis revealed tissue consistent with neuroendocrine carcinoma. Despite complete medical workup, no other primary MCC could be detected. While being an atypical presentation, the tumor mass showed an excellent response to the combination of chemotherapy followed by radiotherapy.